Addressing the Challenges of Palliative Care for Homeless Veterans. (March 2018) - Hutt, Evelyn; Albright, Karen; Dischinger, Hannah; Weber, Mary; Jones, Jacqueline; O'Toole, Thomas P.
Background: Veterans who nearing the end of life (EOL) in unstable housing are not adequately served by current palliative care or homeless programs. Methods: Multidisciplinary focus groups, interviews with community and Veterans Affairs (VA) leaders and with 29 homeless veterans were conducted in five cities. A forum of national palliative and homelessness care leaders (n=5) and representatives from each focus group (n=10), then convened. The forum used Nominal Group Process to suggest improvements in EOL care for veterans without homes. Modified Delphi Process was used to consolidate and prioritize recommendations during two subsequent tele-video conferences. Qualitative content analysis drew on meeting transcripts and field notes. Results: The Forum developed 12 recommendations to address the following barriers: (1) Declining health often makes independent living or plans to abstain impossible, but housing programs usually require functional independence and sobriety. (2) Managing symptoms within the homelessness context is challenging. (3) Discontinuities within and between systems restrict care. (4) VA regulations challenge collaboration with community providers. (5) Veterans with unstable housing who are at EOL and those who care for them must compete nationally for prioritization of their care. Conclusion: Care of veterans at EOL without homes may be substantially improved through policy changes to facilitate access to appropriate housing and care; better dissemination of existing policy; cross-discipline and cross-system education; facilitated communication among VA, community, homeless and EOL providers; and pilot testing of VA group homes or palliative care facilities that employ harm reduction strategies.